LECTURERS' PERFORMANCE IN INCREASING OF LEARNING QUALITY THROUGH SELF-MONITORING EVALUATION - Andi Rahman (STAI Hubbulwathan Duri, 2020)
The research objective was to get the use of teachers’ self-monitoring strategies in conducting performance evaluations, so that the quality of learning in class becomes high quality. The research method used descriptive qualitative. Data collection techniques used observation and interviews. The data analysis technique consists of three stages, namely data reduction, data presentation, and drawing conclusions. The research was conducted at the Ahmad Dahlan Institute of Technology and Business Jakarta. The results showed that the teacher always evaluated the performance of the learning and teaching process on a regular basis, namely at the end of each semester. This is done to evaluate the overall learning outcomes. Meanwhile, learning evaluation is also carried out after each learning process by students’ input. The implication of the research results is the development of a teacher’s performance evaluation system at the University, either carried out by individual or university leaders